SOCIAL LIFE: NEW REFORMS. CINEMA, THEATRE, MUSEUMS, SPORTS, OUTSTANDING SPORTSMAN OF UZBEKISTAN AND THEIR CONTRIBUTION TO DEVELOPMENT OF SPORTS - Teshaboyeva Nafisa Zubaydulla qizi; Tulayeva Malikabonu Erkin qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article examines the post-independence reforms in Uzbekistan in the fields of culture and sports. It highlights the development of cinema, theatre, museums, and sports infrastructure, and discusses how these reforms have improved social life, cultural engagement, and national pride. The article also underlines the role of prominent Uzbek athletes in inspiring youth and advancing sports.